Synthesis of Some New Substituted 1,3,4-Oxadiazole and 1,3,4-Thiadiazole Derivatives - Amena A. Ahmed (College of Education for Pure Sciences, 2018)
In this paper the synthesis of five membered ring heterocyclic compounds was achieved, 2-(8-chloro naphtoyl) benzoic acid (1) was used as starting material which was prepared from the condensation of 1- chloro naphthalene with phthalic anhydride in presence of anhydrous aluminum chloride, the acid was then esterified to the corresponding ethyl ester(2). The ester(2) was converted to the corresponding hydrazide(3) then cyclized into substituted 1,2,4 triazole. The hydrazice(3) was treated with ammonium thiocyanate in presence of concentrated hydrochloric acid to give substituted thiosemicarbazide(7) which was converted to 1,3,4- thiadiazole (8) in acidic medium. While in oxidation with HgO the product was oxadiazole(9). This was converted to a Schiff base(10) followed by cyclization to the corresponding thiazolidine derivative(11). Compound (1) was also converted to ethyl ester (13) via acid chloride (12), which was treated with hydrazine hydrate in ethanol to give the corresponding hydrazide (14) which converted to oxadiazole(16) and thiazolidine(17). Compound (19) was synthesized from compound (1) by its reaction with hydrazide (18) then it was cyclized by phosphorus oxychloride. The structures of synthesis compound were confirmed by spectral and physical methods.